The Effect of Using Ethics Poster Media On The Disipline Of 5-6 Years Old Children At Aminah Tuzzuhriyah Kindergarten, Palembang - Desi Fitriyana; Amir Hamzah; Izza Fitri (Jurusan Tarbiyah,IAIN PALANGKARAYA, 2026)
This study aims to investigate the effect of using ethical poster media on improving the discipline of children aged 5–6 years at TK IT Aminah Tuzzuhriyah. A quantitative approach with a pre-experimental one-group pretest–posttest design was employed. The participants consisted of 12 children from the El-Hakim group. Data were collected using an observation checklist and a discipline assessment rubric, supported by documentation analysis. The effectiveness of ethical poster media was analyzed through validity, reliability, normality, and homogeneity tests, followed by a t-test. The results revealed a significant difference between the pretest and posttest scores, with the pretest mean = 15 and the posttest mean = 32.3. These findings indicate an improvement in children’s discipline after the intervention. The t-test result, t(11) = 30.84, p < 0.05, further demonstrates that the use of ethical poster media has a statistically significant effect on improving discipline in early childhood. In conclusion, ethical poster media is an effective instructional medium for supporting the development of discipline in early childhood education settings.